2014
DOI: 10.1007/s10661-014-3661-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and validating the temporal dynamics of interday streamflow from two upland head micro-watersheds with different vegetative conditions during dry periods of the growing season in the Bohemian Massif, Czech Republic

Abstract: At present, dynamic land use, climate change, and growing needs for fresh water are increasing the demand on the ecosystem effects of forest vegetation. Mountainous areas are at the forefront of scientific interest in European forest ecology and forest hydrology. Although uplands cover a significant area of the Czech Republic and other countries and are often covered with forest formations, they do not receive an appropriate amount of attention. Therefore, two experimental upland head micro-watersheds in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It may be therefore possible that the daily amplitude is mostly dependent on the vegetation in the catchment. Moreover, results from a close treeless catchment (Deutscher and Kupec, ) showed amplitudes approaching 40%, pointing out regulatory role of the forests on the dynamics of water discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be therefore possible that the daily amplitude is mostly dependent on the vegetation in the catchment. Moreover, results from a close treeless catchment (Deutscher and Kupec, ) showed amplitudes approaching 40%, pointing out regulatory role of the forests on the dynamics of water discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of streamflow during short precipitation‐free periods of the growing seasons in 2 years 2011 (Deutscher and Kupec, ) and 2012 indicated that the year 2011 was wetter than 2012. In 2011, the mean observed streamflow reached 0.8 l s −1 versus 0.4 l s −1 in 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show harmonic evapotranspiration rates that have orders of magnitude, which are smaller than the levels assessed on typical catchments (Kirchner 2006(Kirchner , 2009Langhammer & Vilimek 2008;Deutscher & Kupec 2014). The problem is thus clearly delimited.…”
mentioning
confidence: 88%
“…Diel fluctuations in streamflow magnitude on days without precipitation input have been identified in catchments around the world, starting as early as the 1930's (for example: Deutscher & Kupec, ; Godwin, ). Several catchment processes can lead to such variations in discharge.…”
Section: Introductionmentioning
confidence: 99%